The improvement of deformability in AA7075 alloy through cryogenic treatment and its correlation with microstructural evolution and FE modelling - Chankitmunkong, Suwaree; Eskin, Dmitry G.; Patakham, Ussadawut; Chancharoen, Wares; Seehanam, Saran; Limmaneevichitr, Chaowalit; Pandee, Phromphong (My University, 2024)
Cryogenic treatment has high potential for improving the deformation behavior through the recrystallization at a low temperature. In this work, true stress–strain curves were obtained via compression tests to understand the deformation behavior of an AA7075 under cryogenic conditions. Results showed a significant improvement in the flow stress of AA7075, increasing from 260 to 560 MPa at the yield point. The strain hardening exponent (n) also increased from 0.25 to 0.35 after deformation at cryogenic temperatures. The presence of Al2CuMg phase influenced the deformation texture of the tested aluminum alloy, resulting in more elongated grains and fine sub-grains after deformation at cryogenic temperatures, due to the hindered recrystallization. Microstructure evolution after deformation at room and cryogenic temperatures was investigated using EBSD technique to characterize texture and recrystallized grains. The results indicated that the spacing of the high-angle grain boundaries (HAGBs) in the sample deformed at room temperature was slightly larger than in the cryogenically treated sample. The alloy deformed at the cryogenic temperature exhibited a higher strain hardening exponent (n = 0.35) compared to room temperature deformation (n = 0.25). Furthermore, finite element analysis supported the experimental findings, showing that the Plastic Equivalent Strain (PEEQ) of the model tested at cryogenic temperature was higher than at room temperature, attributed to grain refinement during low-temperature deformation. The calculated effective stress responses at cryogenic temperatures for the investigated flow stress aligned well with the experimental results. These new aspects and mechanisms of deformation of aluminum alloys at cryogenic temperatures can improve the formability of high-strength alloys in the future production of more complex and integrated lightweight components.
Keywords: Al2CuMg phase; Plastic Equivalent Strain (PEEQ); Recrystallization; True stress-strain curves